2016
DOI: 10.1007/s11255-016-1449-y
|View full text |Cite
|
Sign up to set email alerts
|

Does steep Trendelenburg positioning effect the ocular hemodynamics and intraocular pressure in patients undergoing robotic cystectomy and robotic prostatectomy?

Abstract: Despite staying in the ST for a long time provided that the ophthalmologic examination was normal, ocular complication risk is low in robotic prostatectomy and cystectomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 24 publications
1
9
0
Order By: Relevance
“…When ST was changed to supine position (T5), IOP recovered to the level similar to that at baseline (T1), although it was slightly elevated again at T6 most probably due to the withdrawal of anesthesia. In addition, we found that the console time significantly affected the increase in IOP during RARP at a cut-off of 4 h. There is another report on the effect of ST on IOP during robotic surgery including 43 RALP cases [6]. The authors found that the highest IOP was at the end of ST under pneumoperitoneum which is in perfect agreement with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…When ST was changed to supine position (T5), IOP recovered to the level similar to that at baseline (T1), although it was slightly elevated again at T6 most probably due to the withdrawal of anesthesia. In addition, we found that the console time significantly affected the increase in IOP during RARP at a cut-off of 4 h. There is another report on the effect of ST on IOP during robotic surgery including 43 RALP cases [6]. The authors found that the highest IOP was at the end of ST under pneumoperitoneum which is in perfect agreement with our findings.…”
Section: Discussionsupporting
confidence: 91%
“…Ischemic optic neuropathy, which is a rare complication, was reported after robotic and laparoscopic radical prostatectomy [54] . Corneal abrasions may occur because of chemosis or exposure keratopathy [55] . Eye patchings and transparent occlusive dressings are recommended to prevent corneal abrasions.…”
Section: Ocular Complications and Edemamentioning
confidence: 99%
“…Recently, several prospective clinical studies have been carried out to evaluate the effects on visual function in patients undergoing RALP . However, most studies excluded patients with pre‐existing ocular diseases, and included healthy patients who were favorable for RALP.…”
Section: Introductionmentioning
confidence: 99%
“…3,4 Recently, several prospective clinical studies have been carried out to evaluate the effects on visual function in patients undergoing RALP. [5][6][7][8][9][10][11][12][13] However, most studies excluded patients with pre-existing ocular diseases, and included healthy patients who were favorable for RALP. Thus far, there has been no prospective assessment regarding RALP for patients with ocular diseases, except for a case report; a glaucomatous patient who underwent RALP without any severe ocular damage was reported on, and how to monitor and manage elevated IOP during RALP was described.…”
mentioning
confidence: 99%